Evaluasi Penerimaan Pengguna terhadap Aplikasi Pengelolaan Kegiatan Harian Sekolah Menggunakan User Acceptance Testing (UAT) - Rahmi Sefrial Dayanti; Denny Kurniadi (Lembaga Yasin AlSys, 2026)
The management of daily school activities plays an important role in supporting the effectiveness of educational processes; however, non-integrated data management can lead to inefficient administrative procedures and hinder information retrieval. This study aimed to evaluate user acceptance of a school daily activity management application using the User Acceptance Test (UAT) method, with a case study at SMP Negeri 2 Solok City. The evaluation was conducted by involving application users as respondents who completed a Likert-scale questionnaire, and the data were then analyzed to determine user acceptance levels by user category. The test results indicated very high levels of acceptance, with UAT scores of 97.6% for subject teachers, 96.4% for duty teachers, 99.1% for guidance and counseling teachers, 93.9% for homeroom teachers, 90.8% for students, and 94.5% for security staff. Overall, the application obtained an average score of 95.4% and was classified in the “very good” category. These findings show that the application is highly accepted by users and is perceived as capable of effectively and systematically supporting the management of daily school activities. The results of this study can serve as a reference for schools in improving the management of school activities and for application developers in further refining the system so that it becomes increasingly optimal in supporting school administration and daily activity management.